2010
DOI: 10.1007/s10518-010-9221-7
|View full text |Cite
|
Sign up to set email alerts
|

Field observations from the Aquila, Italy earthquake of April 6, 2009

Abstract: On April 6, 2009 an earthquake of Magnitude 6.2 (M w ) struck the Abbruzzo region of Italy causing widespread damage to buildings in the city of L'Aquila and surrounding areas. This paper summarizes field observations made by the Earthquake Engineering Field Investigation Team (EEFIT) after the event. The paper presents an overview of seismological and geotechnical aspects of the earthquake as well as a summary of the observed damage to buildings and infrastructure. A brief overview of the earthquake casualtie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 14 publications
3
18
0
1
Order By: Relevance
“…Because of their importance in the management of the emergency response, medical centers must be designed to achieve high performance levels under severe ground motions. Unfortunately hospitals have proven to be as vulnerable to earthquakes as the population they serve, and in the last decades, moderate or heavy structural damages to medical complexes were reported after ground motions in California, Japan, Iran, India and Italy (USGS -United States Geological Survey, 1996;Achour et al, 2011;Rossetto et al, 2011). Besides, past experience showed that the operation of a healthcare center as a whole depends on the integrity of all its physical components, including not only the structural frame, but also non-structural components (NSCs) and technological content (TC), such as architectural elements and utilities, and medical equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their importance in the management of the emergency response, medical centers must be designed to achieve high performance levels under severe ground motions. Unfortunately hospitals have proven to be as vulnerable to earthquakes as the population they serve, and in the last decades, moderate or heavy structural damages to medical complexes were reported after ground motions in California, Japan, Iran, India and Italy (USGS -United States Geological Survey, 1996;Achour et al, 2011;Rossetto et al, 2011). Besides, past experience showed that the operation of a healthcare center as a whole depends on the integrity of all its physical components, including not only the structural frame, but also non-structural components (NSCs) and technological content (TC), such as architectural elements and utilities, and medical equipment.…”
Section: Introductionmentioning
confidence: 99%
“…The observation in the field on building materials was implemented based on four categories: namely wood, wood + concrete, traditional brick, reinforced concrete with the brick infill walls, and concrete + steel. The levels of damage to buildings were found principally related to the construction type [37,14,12,15,31,40,41]. In observational studies, it was found that the most resistant structures are made from reinforced concrete and double or single bricks.…”
Section: Construction Materialsmentioning
confidence: 99%
“…The earthquakes, which have struck the Emilia Romagna region, can be classified as an inter-regional disaster [10] [11] -that required coordination at the national level -because it involved more than 80,000 people distributed across 40 municipalities (16 in the Province of Modena, 7 in Mantua, 7 in Bologna, 6 in Ferrara, and 4 in Reggio Emilia) and it damaged historic buildings in the largest towns (Ferrara, Mantua, Modena and Bologna). The civil protection of the Emilia-Romagna region is one of the best-equipped and organised in Italy, with a big headquartered in Bologna and huge number of vehicles, manpower, equipment, and supplies.…”
Section: Management Of the Emergency Response In Emiliamentioning
confidence: 99%